2022
DOI: 10.1088/1538-3873/ac77bd
|View full text |Cite
|
Sign up to set email alerts
|

The JWST Early Release Science Program for the Direct Imaging and Spectroscopy of Exoplanetary Systems

Abstract: The direct characterization of exoplanetary systems with high-contrast imaging is among the highest priorities for the broader exoplanet community. As large space missions will be necessary for detecting and characterizing exo-Earth twins, developing the techniques and technology for direct imaging of exoplanets is a driving focus for the community. For the first time, JWST will directly observe extrasolar planets at mid-infrared wavelengths beyond 5 μm, deliver detailed spectroscopy revealing much more precis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 230 publications
0
27
0
Order By: Relevance
“…Future missions such as the JWST and Ariel (Tinetti et al 2018) will provide higher sensitivity and/or wider spectral coverage than HST/WFC3. This will have a huge impact on the detection of atmospheric features on small exoplanets, even with the presence of clouds at high altitudes (Constantinou & Madhusudhan 2022;Hinkley et al 2022;Whittaker et al 2022). If there is a significant amount of HCN in the atmosphere of L 98-59 b, we should be able to detect a very strong absorption feature near 2.5 μm, which is covered by the wavelength ranges of instruments from both of JWST and Ariel.…”
Section: Future Missionsmentioning
confidence: 99%
“…Future missions such as the JWST and Ariel (Tinetti et al 2018) will provide higher sensitivity and/or wider spectral coverage than HST/WFC3. This will have a huge impact on the detection of atmospheric features on small exoplanets, even with the presence of clouds at high altitudes (Constantinou & Madhusudhan 2022;Hinkley et al 2022;Whittaker et al 2022). If there is a significant amount of HCN in the atmosphere of L 98-59 b, we should be able to detect a very strong absorption feature near 2.5 μm, which is covered by the wavelength ranges of instruments from both of JWST and Ariel.…”
Section: Future Missionsmentioning
confidence: 99%
“…By comparing the luminosity of VHS 1256 b with evolutionary tracks, Dupuy et al (2022) found the companion's mass to be 11.8 ± 0.2M Jup or 16 ± 1M Jup , depending on the model choices. It is also among the first targets to be observed by JWST as part of an Early Release Science program (Hinkley et al 2022). In time-resolved observations, VHS 1256 b has exhibited high amplitude brightness and spectral variability (e.g., Bowler et al 2020;Zhou et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using the on-sky JWST/NIRCam F444W contrast curve from Carter et al (2022) in the JWST ERS-1386 program (Hinkley et al 2022), we calculate the expected on-sky contrast for Vega with NIRCam F440W in Fig. 2 for JWST GTO-1193 observations as follows.…”
Section: Implications For Jwst Observationsmentioning
confidence: 99%